2018
DOI: 10.9779/puje.2018.209
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Resilience and Gender in the Relationship between Adults Childhood Traumatic Experiences and Psychological Symptoms

Abstract: This study examined the mediating role of resilience and gender in the relationship between adults' childhood period traumatic experiences and psychological symptoms. The participants of the research consisted of 276 adults, from whom data were collected using the Short Symptom Inventory, the Traumatic Childhood Experiences Scale, and the Adult Resilience Scale. Confirmatory factor analysis was applied, along with path analysis and mediator test. Results indicated that adults' childhood traumatic experiences h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Another result of the current study is that a positive and significant relationship was found between positive childhood experiences and psychological resilience. Our findings are consistent with those of previously reported findings (Dogan & Yavuz, 2020); However, studies have reported a significant negative relationship between negative childhood experiences and psychological resilience (Aziz & Yıldırım, 2020;Howell et al, 2020;Kelifa et al, 2020;Poole et al, 2017;Savi Cakar, 2018). These results show that both positive and negative childhood experiences affect the development of psychological resilience.…”
Section: Discussionsupporting
confidence: 93%
“…Another result of the current study is that a positive and significant relationship was found between positive childhood experiences and psychological resilience. Our findings are consistent with those of previously reported findings (Dogan & Yavuz, 2020); However, studies have reported a significant negative relationship between negative childhood experiences and psychological resilience (Aziz & Yıldırım, 2020;Howell et al, 2020;Kelifa et al, 2020;Poole et al, 2017;Savi Cakar, 2018). These results show that both positive and negative childhood experiences affect the development of psychological resilience.…”
Section: Discussionsupporting
confidence: 93%
“…By combining the results of all items in the RSA test after eight of them, a total RSA score can be determined. (16). Savi et al reported the Cronbach's Alpha value of the scale as 0.71.…”
Section: Data Collection Toolsmentioning
confidence: 99%